The Religiosity of the Managers and Management of the Laz Sinergi Foundation in Collecting Waqf - Hendi Suhendi; Asep Muhyiddin (Program Studi Studi Agama-Agama Pascasarjana UIN Sunan Gunung Djati Bandung, 2026)
This study addresses the gap between the potential of waqf (Islamic endowment) in Indonesia and the low level of actual collections, the scarcity of research linking administrators' religiosity to waqf management, and the shifting orientation of waqif (donors) toward practical benefits. Focusing on the LAZ Sinergi Foundation, the study examines how administrators' religiosity, religious values, and their application in waqf management influence fundraising. Employing an interdisciplinary qualitative ethnographic approach, the research integrates religiosity theory—specifically the dimensions of knowledge, experience, and consequences—with organizational values, ethics, and waqf management practices. Data were gathered through participant observation, in-depth interviews, and researcher engagement. The findings reveal that the administrators' religiosity shapes their understanding of waqf as a religious trust (knowledge), fosters a sense of responsibility and trustworthiness (experience), and manifests in concrete management actions (consequences). These values ​​are internalized within the organization's culture and governance, resulting in practices that are not merely administrative but also morally significant. The administrators' religiosity strengthens organizational integrity, builds public trust, encourages donor participation, and—through socially impactful programs—sustains waqf collection efforts. This study contributes to the field by integrating religiosity and management aspects to develop a waqf governance model that is adaptive, integrity-based, and welfare-oriented.